Resting Heart Rate and Risk of Incident Heart Failure: Three Prospective Cohort Studies and a Systematic Meta‐Analysis - Khan, Hassan (J Am Heart Assoc, 2015)
BACKGROUND: The relationship between resting heart rate (RHR) and incident heart failure (HF) has been questioned. METHODS AND RESULTS: RHR was assessed at baseline in 7073 participants in 3 prospective cohorts (Cardiovascular Health Study, Health ABC study and Kuopio Ischemic Heart Disease Study) that recorded 1189 incident HF outcomes during 92 702 person‐years of follow‐up. Mean age of participants was 67 (9.9) years and mean RHR was 64.6 (11.1) bpm. Baseline RHR correlated (P<0.001) positively with body mass index (r=0.10), fasting glucose (r=0.18), and C‐reactive protein (r=0.20); and inversely with serum creatinine (r=−0.05) and albumin (r=−0.05). Baseline RHR was non‐linearly associated with HF risk. The age and sex‐adjusted hazard ratio for HF comparing the top (>72 bpm) versus the bottom (<57 bpm) quartile of baseline RHR was 1.48 (95% confidence interval [CI] 1.26 to 1.74) and was modestly attenuated (1.30, 95% CI 1.10 to 1.53) with further adjustment for body mass index, history of diabetes, hypertension, smoking status, serum creatinine, and left ventricular hypertrophy. These findings remained consistent in analyses accounting for incident coronary heart disease, excluding individuals with prior cardiovascular events, or those taking beta‐blockers; and in subgroups defined by several individual participant characteristics. In a pooled random effects meta‐analysis of 7 population‐based studies (43 051 participants and 3476 HF events), the overall hazard ratio comparing top versus bottom fourth of RHR was 1.40 (95% CI: 1.19 to 1.64). CONCLUSIONS: There is a non‐linear association between RHR and incident HF. Further research is needed to understand the physiologic foundations of this association.